Going slow to go fast: landscape designs to achieve multiple benefits - Manley, Patricia N.; Bistritz, Liraz; Povak, Nicholas A.; Day, Michelle A. (Frontiers in Environmental Science, 2025)
IntroductionGrowing concerns about fire across the western United States, and commensurate emphasis on treating expansive areas over the next 2 decades, have created a need to develop tools for managers to assess management benefits and impacts across spatial scales. We modeled outcomes associated with two common forest management objectives: fire risk reduction (fire), and enhancing multiple resource benefits (ecosystem resilience).MethodWe evaluated the compatibility of these two objectives across ca. 1-million ha in the central Sierra Nevada, California. The fire strategy focused on short-term fire risk reduction, while the ecosystem strategy focused on longer-term resilience. Treatment locations were selected using a spatial optimization model, ForSys, and each scenario was evaluated at two levels of accomplishment: 50% and 75% of each landscape unit in desired condition across the landscape.ResultsAt the 50% threshold level, the hectares selected were complementary, with little overlap in treated areas between the fire and ecosystem scenarios. Additional hectares needed to reach the 75% threshold level, however, overlapped substantially between the two scenarios, indicating that tradeoffs are required to reach the 75% level for either objective. We then compared the ability of each scenario to contribute to their respective objectives, including individual socio-ecological outcomes (four pillars) and overall resilience based on the Framework for Resilience. The Fire scenario primarily benefited fire-risk reduction to communities in the wildland urban interface. In contrast, the Ecosystem scenario exhibited the greatest improvements in forest resilience, carbon, and biodiversity, but did not perform as well for reducing fire risk to communities.DiscussionShort-term fire risk reduction and long-term resilience objectives can be complementary within a landscape, but ecosystem resilience is not a guaranteed co-benefit when fire risk reduction is the primary objective. Rather, improving ecosystem resilience cannot be achieved quickly because many desired forest conditions require both deliberate strategic action to guide the location, character, and timing of management as a disturbance agent, as well as adequate time for landscape conditions to improve and resilience benefits to be realized.